Advanced evaluation of hidradenitis suppurativa with ultra‐high frequency ultrasound: A promising tool for the diagnosis and monitoring of disease progression. Issue 4 (11th December 2019) - Oranges, Teresa; Vitali, Saverio; Benincasa, Bianca; Izzetti, Rossana; Lencioni, Riccardo; Caramella, Davide; Romanelli, Marco; Dini, Valentina
Abstract: Background: Hidradenitis suppurativa is a chronic inflammatory skin disease. An ultrasound staging (SOS‐HS) using frequencies from 7 to 18 MHz has been proposed to evaluate the severity of the disease. Materials and methods: We retrospectively evaluated the most significant lesions in 50 patients with hidradenitis suppurativa (32 females and 18 males, aged from 12 to 68 years old), who had undergone high‐frequency ultrasound (HFUS) (18‐22 MHz) and ultra‐high frequency ultrasound (UHFUS) (48 and 70 MHz). A MyLab™ Touch system (Esaote) equipped with a 18‐22 MHz linear probe was used for the HFUS, and a Vevo ® MD (VisualSonics) was used for the UHFUS, equipped with two linear probes (70 and 48 MHz). Results: A total of 116 lesions were observed, of which 66 were fluid collections, 32 were tunnels, 6 pseudocysts, 5 bridge scars, 5 tombstone comedones, and 2 granulation tissues. Structures that had already been described with HFUS were then observed with UHFUS but with a better definition. In addition, structures that had not been detected by HFUS were also observed with UHFUS such as drop‐shaped hair follicles, micro‐tunnels, and microcysts. Conclusion: Ultra‐high frequency ultrasound provides a better understanding of hidradenitis suppurativa. Patients can be monitored more effectively thereby preventing the most severe changes.